2010
DOI: 10.1002/pssb.201000135
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of functionalized nanotubes, graphene and nanowires: from ab initio to mesoscopic physics

Abstract: We review recent theoretical results aiming at understanding the impact of doping and functionalization on the electronic transport properties of nanotubes, nanowires and graphene ribbons. On the basis of ab initio calculations, the conductance of micrometer long tubes or ribbons randomly doped or grafted can be studied, allowing to extract quantities at mesoscopic length scales such as the elastic mean free path and localization length. While the random modification of a 1D conducting channel leads generaly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…For this purpose, we favor HfS 3 , In 4 Se 3 , In 4 Te 3 , or the electron gas that forms at the surface/interface of InP and InAs as SOC channel materials, because they are likely to be scalable to spatial channel widths of 10 nm or less. Concern about edge scattering has attracted the attention of theorists [60]- [65] and has been found to have a major influence in experiment [66]- [68]. The trichalcogenides, MX 3 , and other transition metal trichalcogenides (TMTCs) such as In 4 X 3 (X = Se, Te) possess a unique quasi-1-D structure that makes devices scaled to dimensions less than nm appear possible.…”
Section: Induced Polarizationmentioning
confidence: 99%
“…For this purpose, we favor HfS 3 , In 4 Se 3 , In 4 Te 3 , or the electron gas that forms at the surface/interface of InP and InAs as SOC channel materials, because they are likely to be scalable to spatial channel widths of 10 nm or less. Concern about edge scattering has attracted the attention of theorists [60]- [65] and has been found to have a major influence in experiment [66]- [68]. The trichalcogenides, MX 3 , and other transition metal trichalcogenides (TMTCs) such as In 4 X 3 (X = Se, Te) possess a unique quasi-1-D structure that makes devices scaled to dimensions less than nm appear possible.…”
Section: Induced Polarizationmentioning
confidence: 99%
“…[20][21][22] By contrast armchair ribbons (AGNR) are semiconducting with width-dependent band gaps and without affinity to magnetic instabilities. [4,[23][24][25][26][27][28][29][30][31] In this letter we further investigate the electronic and atomistic structure of mono-hydrogenated AGNRs and show that interesting quantum effects arise, nevertheless. We formulate selection rules for the transverse momenta of the ribbon.…”
mentioning
confidence: 99%
“…Previous experiments, in which defects were created by ion irradiation, indicate that for long CNTs the strong localization regime can be achieved, where the conductance decreases exponentially with the CNT length [9]. This was also studied theoretically for different defect types [17][18][19][20][21][22], especially for vacancies [23][24][25][26][27], and also for other materials like silicon nanowires [28]. First analytic derivations of White and Todorov showed that the localization exponent depends linearly on the tube diameter [29].…”
Section: Introductionmentioning
confidence: 92%